Pendampingan dan Peningkatan Pengetahuan Filsafat Pada Anak Muda NU Di Kabupaten Nganjuk - Budi Harianto; Nurul Syalafiyah (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2026)
This mentoring and philosophical knowledge enhancement program aims to foster critical and intellectual awareness among Nahdlatul Ulama (NU) youth in Nganjuk Regency. Philosophy, as a discipline that sharpens reasoning, logic, and deep understanding of reality, is considered essential in strengthening the intellectual foundation of young generations, especially in responding to contemporary challenges. Through open discussions, classical text studies, and critical thinking training, this program has successfully increased participants’ interest in and understanding of both Islamic and Western philosophy. The mentoring results indicate improved active participation, argumentative skills, and critical reflection in socio-religious life. Moreover, this activity strengthens the intellectual identity of NU youth as a future generation that is not only religious but also rational and open to dialogue. Additionally, the program creates an inclusive alternative learning space and promotes a culture of healthy thinking among NU youth. It serves as a relevant and applicable model of community-based intellectual development, which can be replicated in other regions with similar characteristics.